Farm Cultural Park as an urban regeneration lab - Fausta Occhipinti (Agathón)
A lot of Italian old town centers are wilderness because of their inability to adapt to the different ways of contemporary living and it represents an urgency that needs compelling solutions. This essay shows the importance of the fieldwork and the involvement of the persons to renew the forsaken town centers through the example of the Farm Cultural Park, a driving force of a cultural, social and economical rebirth of the Sicilian town of Favara.